A Morphological Study of Assimilation of Atlas Vertebrae and their Clinical Implications in Indian Population - Nishigandha Sadamate; Ravindra Vedpathak; Vilas Chimurkar (Journal of Pharmacy and Bioallied Sciences)
Background: Atlas is the first cervical vertebra. Rarely, does the atlas vertebra fuse with the occipital bone, and this occipitalization of the atlas is known as the assimilation of the atlas. Congenital fusion of the atlas with the occipital bone is the common denominator of a galaxy of skull defects, several examples of bony distortion of the foramen magnum were reported by early anatomists. Materials and Method: A total of 210 dry skulls of unknown sex and age from Dr. Rajendra Gode Medical College, Amravati, Department of Anatomy, and various other medical, Dental, and Ayurveda colleges from Amravati were studied. Each skull was carefully observed for variations. Result: During the study, we observed Atlanto-occipital assimilation in 2 skulls. One skull showed complete occipitalization and another skull showed partial occipitalization meaning a bifid posterior arch. Conclusion: Detection and treatment of this deformity are essential as this deformity often causes cervical spine instability.